2018
DOI: 10.1016/j.pulmoe.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic respiratory failure in patients with chronic obstructive pulmonary disease under home noninvasive ventilation: Real-life study

Abstract: This is a real-life retrospective study in COPD patients with CHRF which results suggest benefit from home NIV. For most, NIV was effective and tolerable even at high pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Durao and co‐workers showed a real‐life study, involved 3 years period, that utilization of NIV for COPD with chronic hypercapnic respiratory failure at home after discharge from ICU decreases the number of admissions for respiratory illness and days spent in hospital 16 . Similarly, we also found that COPD patients previously using home‐based NIV had less risk for NIV failure at ICU stay.…”
Section: Discussionsupporting
confidence: 70%
“…Durao and co‐workers showed a real‐life study, involved 3 years period, that utilization of NIV for COPD with chronic hypercapnic respiratory failure at home after discharge from ICU decreases the number of admissions for respiratory illness and days spent in hospital 16 . Similarly, we also found that COPD patients previously using home‐based NIV had less risk for NIV failure at ICU stay.…”
Section: Discussionsupporting
confidence: 70%
“… 12 In patients who underwent a sleep study before initiating HMV (65.6%), we found a prevalence of OSA of 46.2% which is in-line with previous studies performed in Portugal. 15 , 16 Soler et al also found a high prevalence of OSA (65.9%) in patients with moderate to severe COPD. 17 These results are considerably different from many RCTs in which presence of obesity or relevant OSA are exclusion criteria for enrolment of COPD patients in HMV studies.…”
Section: Discussionmentioning
confidence: 94%
“…[2,14,[16][17][18] In studies, patient compliance with NIMV treatment has been reported as 77% to 96% and the results were generally good. [2,5,[18][19][20] Örnek et al [7] found that the daily duration of NIMV use was statistically longer in patients with a shorter life span than those for whom it was longer. In our study, NIMV compliance was found to be 100% in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the use of NIMV at home have evaluated device use compliance in COPD patients and other disease groups. [2,[5][6][7] However, data on patient compliance with this treatment are limited to patients with and without emphysema. [8] The present study is an examination of whether COPD patients with emphysema were less compliant with domiciliary NIMV therapy than COPD patients without emphysema.…”
Section: Introductionmentioning
confidence: 99%